Prevalence of white coat hypertension (WCH) among individuals with elevated clinic blood pressure: A feasibility study - Jing Yi Lim; Prawira Oka; Lynette Ong; Jannathnisha Binte Mohideen Pitchay; Wei Ling Ng (Proceedings of Singapore Healthcare)
Background White coat hypertension (WCH) is characterized by elevated clinic blood pressure (BP) measurements and normal out-of-clinic readings. Once considered benign, emerging evidence suggests WCH is associated with increased cardiovascular risk and mortality. Methods This feasibility study was conducted at a primary care clinic in Singapore between November 2019 and October 2023. Individuals with elevated clinic BP were recruited through convenience sampling. Data was collected across two visits via an interviewer-administered questionnaire and a weeklong self-measured BP monitoring program. Home BP readings were interpreted utilizing three methods: (1) average of all readings, (2) 2018 ESH/ESC guidelines, and (3) clinician “eyeball method”. WCH was diagnosed in individuals with elevated clinic BP readings and normal home BP readings. Results Sixty individuals were recruited, with a mean age of 61.8 ± 9.6 years, most were Chinese (90%) and married (63%). Nearly half the participants had hyperlipidemia with 56.7% overweight or obese. WCH was diagnosed in 23.3% of participants, while 35% were newly diagnosed with hypertension. None of the individuals with WCH reported significant anxiety as assessed using the GAD-7 scale. The clinician “eyeball method” resulted in five more individuals being diagnosed with hypertension compared to the 2018 ESH/ESC method. Conclusion Over half of individuals with elevated clinic BP had WCH or undiagnosed hypertension. Primary care physicians should promote home BP self-monitoring and adopt standardized guideline-based methods for home BP interpretation. Future research should explore practical strategies to assimilate guidelines to real-world practice, improving diagnostic accuracy and treatment.